Widespread early Holocene deglaciation, Washington Land, northwest Greenland. (1st March 2020) - Ceperley, Elizabeth G.; Marcott, Shaun A.; Reusche, Melissa M.; Barth, Aaron M.; Mix, Alan C.; Brook, Edward J.; Caffee, Marc
Abstract: Constraining the Greenland Ice Sheet (GIS) response to past climate change is imperative for understanding modern ice sheet sensitivity to rising temperatures. In this study, we investigate the response of the GIS to warming during the last deglaciation across the currently ice-free area of Washington Land in northwest Greenland. We apply 10 Be cosmogenic surface exposure dating to glacially-transported boulders deposited across the landscape, the interpretation of the dates offering insight into GIS retreat after the Last Glacial Maximum. We find that the northwestern sector of the GIS sustained full ice cover across Washington Land until ∼11 ka, then began thinning, with widespread ice retreat culminating by 8.5 ± 1.1 ka. The record of our new exposure ages indicates that deglaciation occurred 2–3 ka after abrupt warming at the end of the Younger Dryas cold period, which suggests a delayed response of the GIS to this regional warming. Highlights: Deglaciation of Washington Land and Nares Strait in northwestern Greenland occured during the Early Holocene at ∼8.5 ka. Deglaciation of northwestern Greenland was 2–3 ka after abrupt warming at the Pleistocene-Holocene transition. Cold-based ice conditions were present at high elevations in Washington Land during the last glacial period.